2(3х+1)-х<3(х+4); 2(х-1)-3(х+2)<6(1+х);
7х+4(х-2)>6(1+3)х;
7(y+3)-2(y+2)>(5y+1)

anasteysha20003 anasteysha20003    2   10.02.2021 16:51    1

Ответы
temirlanrashid temirlanrashid  12.03.2021 16:57

ответ:2(3x + 1) - x ≤ 3(x + 4), 2) 7x + 4(x - 2) > 6(1 + 3x),

6х + 2 - х ≤ 3х + 12, 7х + 4х - 8 > 6 + 18x,

5х + 2 ≤ 3х + 12, 11x - 8 > 6 + 18x,

5х - 3х ≤ 12 - 2, 11x - 18x > 6 + 8,

2х ≤ 10, -7x > 14,

х ≤ 5, x < - 2,

х ∈ (-∞; 5]; x ∈ (-∞; -2);

3) 2(x - 1) - 3(x + 2) < 6(1 + x), 4) 7(y + 3) - 2(y + 2) ≥ 2(5y + 1),

2x - 2 - 3x - 6 < 6 + 6x, 7y + 21 - 2y - 4 ≥ 10y + 2,

-x - 8 < 6 + 6x, 5y + 17 ≥ 10y + 2,

-x - 6x < 6 + 8, 5y - 10y ≥ 2 - 17,

-7x < 14, -5y ≥ -15,

x > -2, y ≤ 3,

x ∈ (-2; +∞); y ∈ (-∞; 3].

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика